Enhancing soybean phosphorus management: integrating cover crop strategies and targeted fertilizer placement and timing - de Oliveira Demarco, Jovani (My University, 2024)
Phosphorus (P) management is essential for promoting soybean growth and maximizing productivity while also reducing the environmental risks associated with nutrient runoff. Cover crops (CC) are considered a promising tool in sustainable agriculture, offering benefits such as improved soil health, enhanced nutrient availability, and better soil moisture dynamics. This thesis investigates two key aspects of P management in soybean production: the influence of cover crops on P management and the effects of different P fertilizer placement techniques. The first study examined how CC impacts P management, soil moisture, and soybean productivity across multiple sites in Kansas during the 2022 and 2023 growing seasons. Using a randomized complete block design with a 3x2 factorial treatment structure, the study compared CC treatments with and without fertilizer application. Results showed that fall-planted triticale produced significantly more biomass than spring-planted oats, especially when fertilized, but increased biomass led to reduced soil moisture at the time of soybean planting. Despite variations in CC biomass and fertilizer use, no significant differences in soybean seed yield were observed across CC and fertilizer treatments. A critical biomass threshold of 2465 kg ha⁻¹ was identified, beyond which soybean yield declined under Kansas environment, highlighting the need for careful management of CC growth and termination timing. Although CC improved overall P accumulation in the soil, they reduced soybean P uptake at the V4 growth stage. Phosphorus application, however, improved P concentration in soybean trifoliate leaves at later stages. The second study focused on optimizing P fertilization techniques by comparing subsurface and broadcast P applications at different rates (45, 90, and 135 kg ha⁻¹) across nine study sites in Kansas. Early season results indicated that subsurface P placement improved P uptake, particularly in soils with low Mehlich-3 soil test P values, but this advantage was diminished by the time of R6 growth stage. No significant differences in P uptake or seed yield were found between subsurface and broadcast treatments at the end of the season. Seed yield analysis showed significant responses to P treatments at only two sites, suggesting that applied P rates frequently exceeded the requirements of the crop for optimal yield. These results emphasize the importance of aligning P application rates with soil P levels and indicate that subsurface placement could offer environmental benefits by reducing P runoff. Overall, this thesis highlights the importance of balanced P management strategies that integrate the benefits of cover crops and precise fertilizer placement to enhance soybean production and promote sustainable agricultural practices. The findings underscore the need for careful management of cover crops to balance biomass growth with moisture retention, as well as the importance of optimizing P application rates to prevent over-application and minimize environmental impacts.
Keywords: Phosphorus; Soybean; Cover crops; Fertilizer placement